Evaluation of Some Haemostatic Parameters among Cement Loaders in Port-Harcourt, Nigeria - Jonathan Nyebuchi; Collins Ohwonigho Adjekuko; Adams Matthew Okur; Evelyn M. Eze (Archives of Current Research International, 2022)
Exposure to cement dust has been serious public health concern with increasing industrial activities in Port Harcourt. This study was aimed at evaluating the effect of cement dust exposure on haemostatic parameters on cement loaders in Port Harcourt. A total of 200 healthy males were recruited for the study; 100 of which were cement loaders and the other 100 were individuals not exposed to cement dust. These subjects were selected randomly at different cement depot in Port Harcourt after consenting to participate in the study. Venous blood was called via venipuncture technique and 5 mls of blood was collected for the laboratory analysis of prothrombin time (PT), activated partial thromboplastin time (APTT), International normalized ratio (INR), D-Dimer, Von-Willebrand factor and fibrinogen. The result showed that there was a significant increase (p-value<0.05) in APTT, VWF, D-Dimer and fibrinogen levels in the cement exposed group but there was no significant difference in PT and INR levels in the exposed group (p-value>0.05). This study has shown that exposure to cement dust affects haemostasis among cement loaders in Port Harcourt.